Postcranial skeleton of Cricosaurus araucanensis (Crocodyliformes: Thalattosuchia): morphology and palaeobiological insights - Herrera, Laura Yanina (2013)
The metriorhynchid crocodyliform Cricosaurus araucanensis (Gasparini & Dellapé) has been documented from Tithonian (Upper Jurassic) strata of the Vaca Muerta Formation exposed in the Neuquén Basin, northwest Patagonia, Argentina. Postcranial components of this species were mentioned but not described in the original analysis. Subsequently, other authors described the forelimbs. The postcranial elements of metriorhynchids are poorly documented in comparison with their skulls, but new data from C. araucanensis reveal delayed ossification of the caudal neurocentral sutures indicating skeletal paedomorphosis affecting not only the appendicular skeleton but also the posterior region of the vertebral column. The morphology of the caudal region (transverse processes of the first caudal vertebrae ventrally deflected) and the reduction in the femur of the fourth trochanter suggest a reduction of the hypaxial musculature allowing increased epaxial musculature. This pattern of musculoskeletal arrangement is consistent with the swimming style and propulsion by lateral undulation of the tail, as proposed by previous authors.